Penerapan Permainan Tradisional Galah Asin (Gobak Sodor) Dalam Pemanasan Pembelajaran Pendidikan Jasmani - Muhammad Fajri Nawawi; Bambang I smaya; Rolly Afrinaldi (Peneliti.net, 2023)
The purpose of making this thesis is to find out the interest in applying the traditional game of galah salty in warm-up physical education learning. This research was conducted at MTS Miftahul Huda Tegalwaru Karawang with a sample of 80 students who were taken as evenly as possible from students in class VII, VIII and IX with a sampling technique that used probability sampling. The research method uses a survey method with a quantitative approach with percentages. The data collection techniques used in this study were documentation and questionnaires. There are stages in this research, namely surveys by participating in teaching students so that they are closer to research objectives while taking documentation, conducting questionnaires with the help of Google from and WhatsApp groups. As for the results of the questionnaire data that has been answered by the respondents, most of the respondents have a high interest as many as 73 student respondents or 91% of the total respondents and 8% or 6 student respondents have quite high interest in the traditional galah salty game and the remaining only 1% or 1 respondent who has a very high interest in the traditional salty galah game, while the interest in this salty galah traditional game is low, very low has a result of 0% of all respondents. So it can be concluded that